Substratos para produção de cogumelos Lentinula edoddes (Shiitake) - Calgaroto, Bruna (2019)
Careful cultivation of mushrooms is a key factor for good growth in your growth. There are over 12,000 species of mushrooms in the world, but not all are for food purposes, only two are for this purpose. The champignon mushroom is the most produced, and followed and species Lentinus edodes) - Shiitake. Shiitake production usually takes place through tree logs. These logs have holes where they are inoculated as seeds. Another way to grow mushrooms is from organic substrates. These substrates can be varied, but must supply the nutrients required by the mushroom. Thus, the objective of this work was to verify the mycelial growth of Lentinus edodes - Shiitake in different organic substrates (pine sawdust, coffee coffee, brewery residual yeast and corn bran). To verify the effect of the variables tested, use a complete experimental design 2 (4-0), with four independent variables at two levels of variation with four repetitions at the center point). According to the proposed experimental design and based on the experimental results, experimental trial 10 shows the best condition for mycelial growth of Lentinus edodes - Shiitake, and the substrate used for its growth consists of 80% pine sawdust and 40% coffee-free corn bran and brewery residual yeast.